Inovasi Pemilahan Sampah di Bank Sampah Induk, Banjarmasin Utara untuk Optimalisasi Produksi Paving Blok: Innovation of a Waste Sorting at the Central Waste Bank in North Banjarmasin for Optimizing Paving Block Production - Raybian Nur; Muhammad Helmy Abdillah; Katiko Imamul Muttaqin (LPPM Universitas Andalas, 2026)
Urban plastic waste management remains a major challenge in many Indonesian cities, including Banjarmasin. The increasing volume of plastic waste has led to material accumulation and limited utilization of shredding residues, particularly high-density plastic fractions that lack economic value. This community service program aimed to improve plastic waste sorting performance in order to optimize the value of plastic shredding residues through the application of appropriate technology. The methodology integrated Participatory Rural Appraisal, Asset-Based Community Development, and Community-Based Technology approaches, involving 14 staff members of the Banjarmasin Municipal Waste Bank from June to November 2025. Technological implementation included the development of a waste sorting device, operational assistance, and training on utilizing plastic residues as raw materials for paving block production. Evaluation was conducted across technical, operational, and partner capacity aspects by comparing conditions before and after program implementation. The results demonstrated a significant improvement in plastic waste sorting performance, reflected in increased sorting capacity, enhanced operational stability, and improved work efficiency. Improvements in operational flow contributed to reduced plastic accumulation and increased utilization of shredding residues for paving block production. Partner capacity also improved, particularly in understanding circular economy principles, technical capability in paving block production, and awareness of business development based on plastic waste utilization. Overall, the application of appropriate technology successfully optimized the value of plastic residues, increased economic added value, and strengthened an integrated urban waste management system based on circular economy principles and community empowerment.